Combination of sporadic inclusion body myositis and primary Sjögren’s syndrome: clinical case and review of literature - Yu. I. Khvan; A. N. Khelkovskaya-Sergeeva (Современная ревматология)
The article presents a review of the literature and a clinical observation of a patient with long-term anamnesis of primary Sjögren's syndrome (SS) in combination with sporadic inclusion body myositis (sIBM). The diagnosis of SS was confirmed in accordance with the Russian diagnostic criteria for SS 2001, as well as with the ACR 2012 and ACR/EULAR 2016 criteria. The diagnosis of sIBM was established on the basis of a characteristic clinical picture: the development of the disease in a woman after 50 years of age with slowly progressive asymmetric muscle weakness and a typical distribution, a moderate increase in the level of creatine phosphokinase (<10 norms for the entire observation period), the presence of a generalized primary muscle process according to needle electromyography, a typical picture of muscle involvement according to magnetic resonance imaging, and the ineffectiveness of high doses of glucocorticoids. The absence of histological confirmation does not contradict the diagnosis, since morphological examination of muscles in patients with a typical course of the disease fails to detect characteristic signs of sIBM in 20% of cases.Currently, there is no effective pathogenetic therapy for sIBM. Understanding the mechanisms of sIBM development will allow to develop effective methods of its treatment.